Adoption of dual-purpose sweetpotato varieties under partial population exposure in Rwanda: Insights from an African plant breeding programme. Issue 3 (16th April 2022) - Danso-Abbeam, Gideon; Baiyegunhi, Lloyd J.S.; Laing, Mark D.; Shimelis, Hussein
Abstract : As part of the Green Revolution, plant breeding programmes such as the African Centre for Crop Improvement have trained scientists to breed crop varieties in Africa to address the challenges of low productivity. However, exposure to and adoption of these varieties is somewhat modest, and there is also a scarcity of empirical studies on the drivers of exposure and adoption. Using data from Rwanda, the counterfactual treatment effect framework was used to estimate observed and potential adoption rates, as well as the drivers of exposure and adoption of dual-purpose sweetpotato varieties bred for both food and feed, under partial exposure to information. The results show that if the entire target farming population had been aware of the varieties, the adoption rate could have been up to 70% instead of the observed rate of 42%, indicating a 28% adoption gap due to partial diffusion. The findings indicate that once these varieties have been exposed, there is scope for further expansion of their cultivation. Key drivers of variety exposure and adoption include membership of farmer groups, participation in demonstration fields, and access to extension services. Thus, conscious efforts to minimize information constraints are a prerequisite for unlocking this adoption puzzle.